Kinematics, dynamics, calibration, and configuration optimization of modular reconfigurable robots - Yang, Guilin (2008)
A modular reconfigurable robot system (MRRS) is a collection of individual link and joint units that can be assembled into various robot configurations for a diversity of task requirements. Such a modularized robotic system can be applied in various scenarios: an individual joint unit can be used as an independent motion control element; fully assembled systems can be used as standard robots with various configurations and degrees of freedom (DOFs). This thesis focuses on the issues pertinent to an MRRS: design, modeling, and optimization.